Comparison of free radicals in blood in pre-operative and post-operative phases of breast malignancies: a clinicopathological study - Jina, Abhishek; Singh, U. C. (International Surgery Journal, 2019)
Background: Various factors have been identified as influencing factors of breast cancer. The free radicals can cause increased oxidative stress by negatively affecting the body’s nucleic acids, lipids and proteins leading to various illnesses including cancer. Therefore, this study was aimed at discovering the progress of treatment of breast carcinoma by exploring the connections of the disease with free radical injury. Methods: The present study was conducted among 30 breast carcinoma patients received in the surgery department of BRD Medical College Gorakhpur. Determination of the levels superoxide dismutase (SOD) (the procedure of photoluminescence), catalase (method of Cavarochi) and the lipid peroxidise was done. The results were presented as mean and standard error (SE). P value of <0.05 was considered as statistically significant. Results: Among the total participants, 73% patients had infiltrating ductal carcinoma and 27% patients had intraductal carcinoma. The dismutase levels showed an increase in the post-operative patients for both the groups. The catalase levels and the lipid peroxide levels showed a reduction in the postoperative patients (p<0.05). Conclusions: The present study result showed that the low amounts of SOD and catalase may not be sufficient to detoxify high amounts of free radicals. The administration of catalase could help in reducing the symptoms. Though, low amounts of SOD and catalase may not be sufficient to detoxify high amounts of free radicals. The administration of enzymes could help in the treatment of breast cancer patients.